Rancang Bangun Mesin Pemotong Tahu Otomatis Berbasis Elektropneumatik dengan Pendekatan Participatory Rural Appraisal dan Eksperimental - Ghozali, Muhamad; Luthfi, Muhammad; Gunawan, Leo Van; Sukroni, Sukroni; Jayamulya, Agus; Rifani, Ari Khoeri (Politeknik Negeri Indramayu, 2025)
ABSTRACT – Manual tofu cutting is often time-consuming and less efficient, necessitating innovation to enhance productivity. This study aims to design an automatic tofu cutting machine as a replacement for the manual cutting process. The method used is Participatory Rural Appraisal (PRA) with an experimental approach. The design process involves simulations to determine the machine's technical specifications, resulting in a minimum pneumatic piston diameter of 24 mm, an inertia of 88,281.25, and a maximum stress of 0.24 N/mm². Testing shows that the machine can cut 112 pieces of tofu in 3.8 seconds. These results indicate that the automatic tofu cutting machine significantly improves the efficiency and speed of the cutting process compared to manual methods. This research contributes to the development of more efficient food processing technology applicable to small-scale industries.